Correlation of serotonin levels in CSF, platelets, plasma, and urine - Audhya, Tapan; Adams, James B.; Johansen, Leah (Biochimica et biophysica acta, 2012)
Neurotransmitter levels are best measured in the cerebrospinal fluid (CSF), but that requires an invasive procedure. Samples were collected from humans and rats. Eighteen women age 38–51years with fibromyalgia provided samples of CSF, plasma, platelets, and urine. Samples of CSF, plasma, platelets, and urine were also collected from Sprague–Dawley rats, adult male, 6months old. One group of rats was treated with p-chlorophenylalanine to decrease their levels of serotonin, and another group of rats was treated with amphetamine to increase their levels of serotonin. Methodological improvements include: 1) the use of siliconized glassware, plasticware, and tubing to prevent adsorption of serotonin, 2) the extraction of serotonin from the CSF, plasma, and platelets, 3) repeated washing of the platelets with an improved buffer, and 4) early morning sample collection. HPLC/MS was used to measure serotonin after extraction. For serotonin, the new method of measuring platelet levels resulted in a very high correlation with levels of serotonin in CSF in rats (r=0.97) and humans (r=0.97). There were lower correlations of levels of serotonin in CSF with levels in plasma (r=0.77 for rats and r=0.57 in humans) and urine (r=0.67 in rats and r=0.62 in humans). This method of measuring serotonin levels in platelets results in a very strong correlation with levels in CSF, so in most cases platelet measurements will be preferable since it is much less invasive to collect. Levels of serotonin in plasma and urine are significantly but less strongly correlated with levels in CSF. ► An improved method of measuring serotonin levels was developed. ► Levels of serotonin in CSF and platelets were highly correlated in humans (r=0.97). ► First study to show high correlation of serotonin in CSF and blood in humans ► Levels of serotonin in CSF and platelets were highly correlated in rats (r=0.97). ► Lower correlations were found for serotonin in CSF vs. plasma or urine.